Local Natural Resources Management in Ghana: The Role of Traditional Authority - Sulemana, Tamara Amina (CGIAR Challenge Program on Water and Food, 2012)
Introduction: in Ghana traditional leaders are considered owners of all natural resources. In that vein, its management cannot be done without them.